the PENERAPAN PEMBELAJARAN PROJECT BASED LEARNING DI SEKOLAH DASAR NEGERI NANGGULAN - Sinta Bella; Havifah Nur Hijatinah; Zulhijrah; Nabila Joti Larasati; Andi Prastowo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Project based learning is an effective and efficient learning method in the learning process. Because student are trained to analyze problems, then carry out exploration, collect information, interpret and assess when working on projects related to the problems being studied. This research aims to find out the process of implementing project based learning at Nanggulan state elementary Scool. Which is in Nanggulan, Maguwoharjo, Depok District. This research uses a qualitative approach while the research method is descriptive. To collect data, researchers used observation, documentation and interviews. Based on data obtained through interviews with class IV homeroom teachers and classroom observations. It is known that a project based learning approach has been implemented. The implementation of project based learning in Nanggulan state elementary schools is carried out through several stages and processes, though planning and implementation stages. The second problem is supporting factors and obstacles to implementing project based learning. According to data obtained by researchers, the supporting factors are adequate infrastructure, professionalism and new enthusiasm, and students’ interest in learning who tend to be more enthusiastic when implementing project based learning. The obstacle to implementing project based based learning is the creation of teaching modules. Obstacles that may be faced in creating teaching modules include limited resources, development skills, and continuous evaluation. Keywords: project based learning, Elementary School Abstrak Project based learning sebagai salah satu pembelajaran yang efektif dan efesien didalam proses pembelajaran. Karena siswa dilatih untuk analisis terhadap permasalahan, kemudian melakukan eksplorasi, mengumpulkan informasi, interprestasi, dan penilaian dalam mengerjakan proyek yang terkait dengan permasalahan yang dikaji. Adapun Penelitian ini bertujuan untuk mengetahui bagaimana proses penerapan pembelajaran project based learning di SDN Negeri Nanggulan. Yang berada di Nanggulan, Maguwoharjo, Kecamatan Depok. Penelitian ini menggunakan pendekatan kualitatif sedangkan metode penelitiannya adalah deskriptif. Untuk pengumpulan data peneliti menggunakan observasi, dokumentasi, dan wawancara. Berdasarkan data yang diperoleh melalui wawancara wali kelas IV dan observasi kelas. Diketahui bahwa telah diterapkan pendekatan project based learning. Penerapan pembelajaran projeck based learning di sekolah dasar negeri nanggulan dilakukan melalui beberapa tahapan dan proses, melalui tahapan perencanaan dan pelaksanaan. Adapun permasalhan kedua yaitu factor pendukung dan hambatan pelaksanaan pembelajaran project based learning. Menurut data yang diperoleh peneliti, factor pendukungnya adalah sarana prasarana yang memadai, profesionalisme dan semangat baru, dan minat belajar siswa yang cenderung lebih semangat saat pelaksanaan project based learning. Adapun hambatan pelaksanaan project based learning adalah pembuatan modul ajar. Hambatan yang mungkin dihadapi dalam pembuatan modul ajar meliputi, keterbatasan sumber daya, keterampilan pengembangan, dan evaluasi dan kontinu. Kata Kunci: Project Based Learning, Sekolah Dasar